THE IMPORTANCE OF CULTURE IN TEACHING ENGLISH (Conferencea, 2022)
It is true that some language learners still feel discomfort while learning stage of English although they have a good command of language skills. There are contexts needed to explain while in teaching process for children. In such situations, cultural factors seem to be one of the main roots of this problematic issue. This chapter, therefore, justifies the importance of teaching cultures in foreign language classrooms. In the same vein, the concept "culture" and key differences between Eastern and Western cultures will be defined and clearly compared. On the other hand, cultural awareness and tradition play important roles in helping young children develop a positive sense of identity and build self-esteem as well as educating them in English. Studies show that cultural appreciation and awareness contribute to building a positive self image and comprehension of another language without difficulties. Reading the following pages will give teachers a greater understanding of culture, its importance in language teaching, considerations and techniques to teach culture effectively.